Methodology of Kitab Al-Jami' Interpretation of the Qur'an by Abdullah Bin Wahb Al-Mishri - Zulfikar, Eko; Rosyad, Aftonur (Aqwal: Journal of Qur'an and Hadis Studies, 2023)
This article attempts to examine the methodology of interpretation in the classic commentary text by Abdullah bin Wahb al-Mishri, namely the book al-Jami' Tafsir al-Qur'an. This is motivated by the existence of a study of ancient manuscripts attributed to Ibn Wahb through transmission. The object of study is al-Jami' Tafsir al-Qur'an by Abdullah bin Wahb al-Mishri which is the result of research (tahqiq and ta'liq) from Miklos Muranyi in 1939. By using a qualitative-descriptive method, this article concludes that: the method used by Abdullah bin Wahb al-Miṣrī can be viewed from 4 points of view; sources of interpretation using bi al-ra'yī, the breadth of explanation uses ijmālī, the goals and systematics use mauḍū'ī and the tendency of interpretation uses bi al-riwāyah. These results indicate that the book of commentaries does not only use a single method in its preparation so that al-Miṣrī makes his book an answer that the compilation of the book of interpretations of the Qur'an is not single, but mono-method, or in methodological terms using comparisons.